2013
DOI: 10.1016/j.jconrel.2013.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Drug delivery to the brain by focused ultrasound induced blood–brain barrier disruption: Quantitative evaluation of enhanced permeability of cerebral vasculature using two-photon microscopy

Abstract: Reversible and localized blood-brain barrier disruption (BBBD) using focused ultrasound (FUS) in combination with intravascularly administered microbubbles (MBs) has been established as a non-invasive method for drug delivery to the brain. Using two-photon fluorescence microscopy (2PFM), we imaged the cerebral vasculature during BBBD and observed the extravasation of fluorescent dye in real-time in vivo. We measured the enhanced permeability upon BBBD for both 10kDa and 70kDa dextran conjugated Texas Red (TR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 43 publications
10
111
0
Order By: Relevance
“…pFUS+MB has been reported to cause hemodynamic alterations in the brain associated with temporary vasoconstriction, as seen with BBBD (31,32). The molecular effects on the NVU associated with BBBD following pFUS+MB have received limited attention.…”
Section: Significancementioning
confidence: 99%
“…pFUS+MB has been reported to cause hemodynamic alterations in the brain associated with temporary vasoconstriction, as seen with BBBD (31,32). The molecular effects on the NVU associated with BBBD following pFUS+MB have received limited attention.…”
Section: Significancementioning
confidence: 99%
“…6,7,11,15,21,25 Based on prior literature, 6,7,10,21 we fixed the MB size to ~2 μm, MB concentration to ~1.7×10 6 bubbles/mL, and sonication time to ~1 minute. Subsequently, we adjusted the voltage and BRR while keeping the duty cycle constant at 5% to generate different acoustic powers.…”
Section: Resultsmentioning
confidence: 99%
“…Nhan et al 25 used two-photon microscopy to investigate the reversible and localized BBB disruption induced by FUS in the presence of MBs by imaging the cerebral vasculature during BBB disruption and observing the extravasation of fluorescently labeled solutes in real-time in vivo. They found that the threshold acoustic pressure for a successful induction in BBB disruption was 0.4-0.6 MPa by combining the MBs with a similar size and a reduced concentration as those used in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations